Tanggung Jawab Hadanah dalam Kasus Pengabaian Anak: Analisis Komparatif Hukum Islam dan Undang-Undang Perlindungan Anak di Indonesia - Fatima Auliyani Almyra Syamal; Fachri Fachrudin; Muhammad Hidayat (Lembaga Yasin AlSys, 2026)
Child neglect in the context of post-divorce hadanah remains a serious issue in Indonesia, particularly because of the weak mechanisms for supervising the implementation of custody decisions and the lack of synchronization between sanctions in Islamic law and criminal instruments in positive law. This study aimed to comparatively analyze the concept and parameters of hadanah responsibility in Islamic law and the Child Protection Law, examine the legal implications for hadanah holders who commit neglect, and formulate an ideal harmonization model to strengthen child protection in Indonesia. This study used a normative juridical approach with a library research method through statutory, shari’a, comparative, and conceptual approaches. The data sources consisted of primary legal materials, including the Qur’an, Hadith, fiqh books, and legislation; secondary legal materials, including journals, books, and tafsir; and tertiary legal materials. The results showed that Islamic law and Law No. 35 of 2014 share common ground in the principle of child welfare, but significant gaps remain in post-decision sanction and supervision mechanisms. This study concludes that hadanah neglect needs to be viewed as a legal violation requiring a systemic response, not merely as a moral violation. The formulated harmonization model includes post-litigation monitoring mechanisms, a tiered sanction system, and standards for evaluating the eligibility of hadanah holders that integrate the principles of maqasid al-shari’ah with the principle of the best interest of the child. The implications of this study emphasize the importance of revising the Compilation of Islamic Law (KHI), strengthening institutional coordination, and developing Islamic family law studies that are more responsive to child protection.